Museums as an Avenue for Enhancing Engagement and Educational Outcomes for Underserved Students. (July 2021) - Elswick, Susan; Delavega, Elena
Museums are the places where we hold treasures for display and study and where learning on a broad range of subjects can occur. However, for many marginalized populations, museums feel off-limits and inaccessible. There is evidence and research to support that exposing "at-risk" youth to programming within museums has a positive and lasting effect across multiple life domains. This article will review one specific museum-based pilot program as an intervention for improving outcomes for "at-risk" youth across domains of self-efficacy and knowledge in the field of science and education. Outcomes as well as recommendations for future replications will be shared.